Intertextual Analysis of Sufaha’ in Q.S. al-Baqarah [2]:13: A study of Wahbah az-Zuhaili and az-Zamakhshari’s Interpretation - Pramana, M. Syarif Adi (Jalsah : The Journal of Al-quran and As-sunnah Studies, 2024)
The purpose of this article is to find a correlation between Wahbah az-Zuhail? and az-Zamakhshar? using Julia Kristeva's intertextuality theory, and then to get an understanding of the interpretation of Sufah?’ according to both mufassir. This article is written using comparative and qualitative methods. The result of this writing is the meaning of Sufah?’ contained in Q. S. al-Baqarah: 13 is the hypocrites who do not want to believe because believers are people who are more intelligent and understand the teachings of religion which are also based on a sense of prestige, pride in the Prophet and the believers. However, they cannot prove what they say, so they are ignorant. The principle of intertextuality in tafsir al-Munir (table I) is included in the category of transposition in the form of parallel, modification, and existence. Then, the principle of intertextuality used in tafsir al-Munir (Table II) is included in the category of transposition in the form of parallel, modification, and expansion.